Ragam Kuliner Masyarakat Medan, Gambaran Sejarah Masuknya Bangsa Asing di Kota Medan - Jufrida Jufrida (Balai Arkeologi Sumatera Utara, 2010)
AbstractThe arrival of foreigners into Medan with the various activities also indirectly affect to the city’s cultural diversity, including culinary. The cultural diversity illustrates that Medan society accept the entry of foreign influences, but adapted to local culture.